Utilization of AR & VR for the Development of Safety Training and Risk Mitigation - Anggraeni, Dwi Puspita (Pt. Anagata Sembagi Education, 2026)
This study examines how Augmented Reality (AR) and Virtual Reality (VR) can be utilized to develop safer and more effective safety training while supporting performance assessment and behavioral change for risk mitigation in high-risk work environments. The background of the study arises from persistent workplace accidents in sectors such as construction, mining, healthcare, emergency response, and industrial processing, where conventional training methods often fail to provide realistic experiential preparation. This research employs a qualitative library research design by analyzing recent accredited journal studies on AR/VR applications in safety training. Data were collected through systematic documentation and analyzed using thematic content analysis focusing on immersive simulation, experiential learning, performance measurement, and behavioral outcomes. The findings show that AR/VR create zero-risk training environments that significantly improve hazard recognition, procedural skills, emergency readiness, and safety awareness compared to traditional approaches. In addition, AR/VR systems enable data-driven performance assessment by tracking user errors, response times, and compliance with safety protocols, fostering continuous improvement. The study concludes that AR and VR function as integrated systems for simulation, evaluation, and behavioral reinforcement, positioning them as strategic technologies for proactive risk mitigation in modern occupational safety management.